Analisis Kebutuhan Rohani dan Strategi PAK bagi Remaja–Pemuda GBI Pondok Daud - Elma Purwantie; Martesa Martesa (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
Youth and youth ministry plays a strategic role in shaping the faith, character, and spiritual maturity of the younger generation. This study aims to analyze the spiritual needs, struggles, and relevant Christian Religious Education (PAK) strategies for youth at GBI Pondok Daud. Using a descriptive qualitative approach, data were obtained through direct observation, interviews with instructors, facility observations, and documentation during worship services. The results indicate that youth are highly enthusiastic about attending worship services and are actively involved in various ministry sectors, such as music, multimedia, and ushering. However, they face several struggles, including academic pressure, the influence of social media, and instability in personal spiritual discipline. Primary spiritual needs include Christian character development, a deeper understanding of God's Word, a supportive community, and consistent spiritual guidance. The implemented PAK strategies, such as creative worship, small group discussions, mentoring, and the use of digital media, have proven effective in addressing the needs of youth. This study concludes that GBI Pondok Daud's youth ministry has been successful, but still needs to strengthen discipleship, improve spiritual discipline, and develop experiential learning activities.